PENERAPAN SISTEM ACTIVITY-BASED COSTING DALAM PENETAPAN HARGA POKOK PRODUKSI TIANG PANCANG PADA PT. MITRAKON ANDAL PRIMA - B51112026, Venny Isvianny (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims to found out traditional cost accounting in determining production main price, found out the calculation of Activity-Based Costing System to determine production main price, and to compare the product cost using traditional cost accounting and using Â Activity-Based Costing System. The method being used in this study would be descriptive study through case study approach the case of PT. Mitrakon Andal prima. The results of this research conducted shows that divergence on calculation and comparison result between traditional cost accounting and Activity-Based Costing System. Triangle pile had overcost or higher product cost charging with Rp17.648.099,99, while for square pile it has undercost or lower product cost charging with Rp17.647.994,87. PT. Mitrakon Andal Prima should expected to reevaluate the system of charges in determining production main price as it will affect the selling price. Keyword: Activity Based Costing System, Cost of Good Manufactured.